Teacher’s Problems in Teaching Listening Online - Niken Yulianti; Desi Wijayanti Ma’rufah (Universitas Perjuangan Tasikmalaya, 2021)
Since the World Health Organization (WHO) declared Covid-19 a pandemic, the education system has been transformed into an online teaching and learning system. This is a big challenge for teachers to teach at home through online media, especially for English teachers in teaching listening online. As we know listening skill is one of the most important English skills for students. This research aims to analyze the teachers’ problems in teaching listening online at Komputama Vocational High School in Jeruklegi, Cilacap. This research is a descriptive and qualitative research. The data were obtained through observation, interviews, and documentation. The result of this research showed there were three problems faced by the teacher: the teacher was hard to find suitable media in preparing the lesson, hard to organize and detect students’ seriousness, and hard to measure students’ listening comprehension. Those problems were also caused by some factors that the researcher qualified into three: students’ network connection or signal, students’ device did not support with the suitable media, and students’ internal factors. The teacher resolves the problems with choosing a suitable application based on the students’ device capability and puts more attention on their students’ learning motivation. Keywords: Teacher’s problems, teaching online, listening class